Lignin derived carbon-alloy-metal oxide heterojunction catalyst and preparation method thereof
By using lignin-derived carbon-alloy-metal oxide heterojunction catalyst, the problems of high overpotential and high cost of noble metal catalysts during hydrogen electrolysis are solved, and high active and low-cost catalysts are achieved, which improves the Efficiency and economicality of electrolytic urea.
Patent Information
- Application Number
- CN202411330772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-24
AI Technical Summary
In the prior art, during the hydrogen electrolysis process of hydrogen production, the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) have high overpotentials, resulting in large energy loss and high cost of precious metal-based catalysts, which limits its wide application.
A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is used to form a high-active, low-cost non-precious metal-based catalyst through solvent thermal synthesis and high-temperature calcination reduction process.
It achieves high catalytic activity and stability, reduces the energy consumption of electrolytic urea, is low in cost and excellent in performance, and is suitable for the treatment of urea wastewater and electrolytic hydrogen production.
Smart Images

Figure CN119433594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical technology, and in particular to a lignin-derived carbon-alloy-metal oxide heterojunction catalyst and a preparation method thereof. Background Art
[0002] The rapid consumption of fossil energy has led to serious problems such as environmental pollution and global warming, forcing people to seek greener and more environmentally friendly clean energy. As one of the sustainable clean energy sources, hydrogen energy has received widespread attention in recent years. Hydrogen production by water electrolysis is one of the most promising and practical technologies among many hydrogen production methods, and it is also a method of hydrogen production that has been studied more. However, the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) have quite high overpotentials, resulting in great energy loss. Although studies have shown that replacing OER with urea oxidation reaction (UOR) can not only reduce the overpotential of the anode, but also treat urea wastewater from industry and agriculture, the HER / UOR performance of the catalyst needs to be further enhanced. Therefore, the development of high-performance HER / UOR bifunctional catalytic materials is particularly important for improving the efficiency of urea electrolysis.
[0003] Precious metal-based catalysts such as Pt / Ir / Ru are currently efficient electrocatalysts for HER / UOR reactions, but their scarce reserves and high prices severely limit the widespread application of precious metals. Therefore, non-precious metal-based catalysts with certain activity and abundant reserves have attracted considerable attention. At the same time, in order to alleviate the consumption of fossil energy, researchers have conducted extensive research on renewable biomass resources. Among them, lignin is the second largest biomass resource in the plant kingdom after cellulose, but its utilization rate is less than 10%. Experimental studies have shown that lignin-derived carbon has the advantages of stable chemical properties, good conductivity, and multiple functional groups, and is considered to be a very promising carbon material.
[0004] The Chinese invention patent with the patent number of 202311156838.5 and the patent name of "Highly Dispersed Lignin-Derived Ru In-situ N-Doped Carbon Material and Its Preparation Method and Application" discloses a catalyst for urea oxidation using lignin as a raw material. However, in this invention patent, the use of precious metal ruthenium as a raw material increases the preparation cost of the catalyst; at the same time, the prepared material is a powder material, which is easy to agglomerate and cause a decrease in catalytic activity.
[0005] Therefore, it is very important to develop highly active and low-cost lignin-derived carbon-chelated non-precious metal-based catalysts. Summary of the invention
[0006] Therefore, it is necessary to provide a high-activity, high-stability and low-cost HER / UOR bifunctional non-precious metal-based catalyst - lignin-derived carbon-alloy-metal oxide heterojunction catalyst and its preparation method.
[0007] To achieve the above object, the inventors provide a method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst, which comprises the following steps:
[0008] 1) dissolving metal salt A and metal salt B in an organic solvent to obtain a mixed solution C;
[0009] The metal salt A is one or a mixture of two or more of the following: chromium salt, manganese salt, iron salt, nickel salt, vanadium salt, cobalt salt, tungsten salt, copper salt, zinc salt, or molybdenum salt;
[0010] The metal salt B is one of the following: molybdenum salt, scandium salt, titanium salt, vanadium salt, chromium salt, zinc salt, gallium salt, germanium salt, strontium salt, yttrium salt, zirconium salt, niobium salt, cadmium salt, indium salt, tin salt, antimony salt, hafnium salt, tantalum salt, tungsten salt, rhenium salt, osmium salt, thallium salt, lead salt, bismuth salt, lanthanum salt, cerium salt, praseodymium salt, neodymium salt, samarium salt, europium salt, gadolinium salt, terbium salt, dysprosium salt, holmium salt, erbium salt, ytterbium salt or thulium salt;
[0011] The metal salt A and the metal salt B are different types of metal salts;
[0012] 2) dissolving lignin in the mixed solution C to obtain a mixed solution D, then adding the mixed solution D and the pretreated carrier into a reactor for a solvothermal reaction at a reaction temperature of 100-200° C. for a reaction time of 4-24 hours, cooling to room temperature after the reaction is completed, taking out the reaction solution in the reactor for filtering, washing the filter cake, and drying to obtain a preliminary sample;
[0013] The input mass ratio of the metal salt A, metal salt B and lignin is 10-26.2:2:1-4;
[0014] The ratio of the input mass of the metal salt A to the surface area of the pretreated carrier is 1-4:9 mg / cm 2 ;
[0015] 3) placing the preliminary sample prepared in step 2) in a calcining furnace, introducing a mixed gas of hydrogen and argon, wherein the volume fraction of hydrogen in the mixed gas is 10-50%, heating the mixture to 400-1000°C at a heating rate of 3-15°C / min, and calcining the mixture at high temperature for 1-5 hours to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0016] The present invention adopts the above scheme, with metal salt A and metal salt B as metal sources, and lignin as carbon source, firstly undergoes solvent thermal synthesis to make lignin and metal ions chelate and coordinate, and then undergoes high-temperature calcination reduction, two or more metal salts A are calcined to form alloys, or metal salt A and part of metal salt B are calcined to form alloys, and metal salt B is calcined to form metal oxides, to obtain a lignin-derived carbon-alloy-metal oxide heterojunction catalyst. The lignin-derived carbon-alloy-metal oxide heterojunction catalyst has high catalytic activity and stability. In particular, in step 1), metal salt A and metal salt B are easy to produce oxides, and are reduced by hydrogen-argon calcination to form alloy-metal oxide heterojunctions.
[0017] The lignin-derived carbon-alloy-metal oxide heterostructure catalyst prepared by the present invention has the following advantages:
[0018] (1) Synergistic effect: In heterogeneous structures, the bonding between the interfaces of different components can increase the electron transfer rate. By combining metal alloys, metal oxides and lignin-derived carbon materials, the final heterogeneous catalyst can be regulated in terms of conductivity, hydrophilicity, chemical stability and active site density.
[0019] (2) Strain effect: In the heterogeneous structure of the present invention, the metal alloy, metal oxide and lignin-derived carbon material cause lattice strains such as tension and compression due to their different chemical compositions and crystal structures, which affects the adsorption energy of the sites to the intermediates and can further improve the catalytic activity of the materials.
[0020] (3) Electronic interaction: In the heterostructure prepared by the present invention, the different arrangements of energy bands of different phases will lead to charge transfer at the interface, which is beneficial to the surface electronic modulation of the heterostructure.
[0021] (4) Good stability: In the present invention, the lignin derivative is used as the carbon source for the carbon coating of the catalyst, which can protect the catalyst in extreme environments and avoid acid and alkali corrosion of the catalyst, so that the prepared catalyst has good stability.
[0022] (5) Structural advantages: Lignin-derived carbon has a three-dimensional network structure and contains a large number of functional groups on its surface, which can greatly improve the catalytic activity of the prepared catalyst. In addition, since lignin-derived carbon is a high-performance and renewable biomass material, the preparation method of the present invention has the advantages of high economic value and environmental protection.
[0023] In the present invention, the metal salt A is a metal salt corresponding to a non-noble metal in the fourth period, and has a controllable electronic structure, which can enhance the HER / UOR performance of the catalyst.
[0024] The preparation process of the present invention is simple and the cost is low. The catalyst prepared by the present invention has good HER and UOR catalytic performance in 1.0 mol / L potassium hydroxide and 0.5 mol / L urea electrolytes, respectively at -10 / -500 / -1000 mA cm -2 and 10 / 500 / 1000mA cm -2 The potentials of -39 / -262 / -356 mV and 1.28 / 1.40 / 1.46 V are shown. Since the catalyst prepared by the present invention has low cost and high activity, it has strong competitiveness in the fields of treating urea wastewater and producing hydrogen by electrolysis.
[0025] Furthermore, the carrier in step 1) is a metal carrier or a non-metal carrier, and the metal carrier is one of the following: a metal mesh, a metal sheet, a metal wire, a metal foil, an alloy mesh, an alloy sheet, or an alloy wire. Using a metal or a non-metal as a carrier can provide a self-growth condition for the lignin-derived carbon-alloy-metal oxide heterojunction catalyst, so that the stability and activity of the catalyst are better.
[0026] Furthermore, the metal mesh is one of the following: nickel mesh, cobalt mesh, copper mesh, iron mesh, titanium mesh;
[0027] The alloy mesh is a nickel-iron mesh or a nickel-molybdenum mesh;
[0028] The metal sheet is one of the following: nickel sheet, cobalt sheet, copper sheet, iron sheet, titanium sheet;
[0029] The alloy sheet is one of the following: nickel-cobalt sheet, nickel-copper sheet, iron-copper sheet, nickel-iron sheet, stainless steel sheet, nickel-molybdenum sheet or nickel-chromium sheet;
[0030] The metal wire is one of the following: nickel wire, cobalt wire, copper wire, iron wire, aluminum wire, titanium wire;
[0031] The alloy wire is nickel-iron wire or nickel-molybdenum wire;
[0032] The metal foil is one of the following: nickel foil, cobalt foil, copper foil, iron foil, zinc foil or titanium foil;
[0033] The non-metallic carrier is one of the following: carbon black tube, carbon nanotube, carbon fiber sheet, activated carbon fiber sheet, carbon nanorod, graphene block, graphene oxide block, activated carbon block, porous carbon block, carbon cloth, carbon felt, glass fiber mesh, layered graphite, organic glass or expanded perlite.
[0034] Further, in the step 3), after the preliminary sample is placed in a calcining furnace for calcination, two or more metal salts A are calcined to form an alloy, or more than one metal salt A and part of the metal salt B are calcined to form an alloy, and the formed alloy is one or a mixture of two or more of the following: NiCo, MoNi, NiFe, NiMn, NiCu, NiCr, NiZn, NiV, NiW, CuCo, CuZn, CuMo, CuFe, CuMn, CuV, CuW, FeCr, FeMn, FeCo, FeZn, FeV, FeW, CoMn, CoZn, CoMo, CoCr, CoV, CoW, NiCoCu, CoCrMo, NiCoMo, NiFeMo, NiMnMo, NiCrMo, NiCuMo, NiCoFe, NiCoZn, NiCoCr, NiCoMn, NiCoV, NiCoW;
[0035] In the step 3), after the preliminary sample is placed in a calcination furnace for calcination, the metal salt B is calcined to form a metal oxide, the metal oxide forms a heterojunction and is loaded on a self-supporting carrier, and the formed metal oxide is one of the following: MoO2, Sc2O3, TiO2, V2O5, CrO3, ZnO, Ga2O3, GeO2, SrO, Y2O3, ZrO2, Nb2O5, CdO, In2O3, SnO2, Sb2O5, HfO2, Ta2O5, WO2, ReO3, OsO2, Tl2O3, Pb3O4, Bi2O3, La2O3, CeO2, Pr2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3.
[0036] Furthermore, the carrier pretreatment method is: the untreated carrier is rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water in sequence, each rinse is performed 3 times, and each rinse time is 20-30 minutes. Through the pretreatment operation, oxides and impurities on the carrier surface are effectively removed.
[0037] Further, the solvent added in step 1) is one of the following: ethanol, ethylene glycol, methanol, isopropanol, glycerol, n-butanol, N,N-dimethylformamide, oleylamine, oleic acid, polyethylene glycol, toluene, acetonitrile, N,N-dimethylacetamide, dimethyl sulfoxide, pyridine, pyrrole, urea, aniline, N-methylaniline, N,N-dimethylaniline, N-ethylaniline, N,N-diethylaniline, diphenylamine, aniline hydrochloride, dioxydimethylpurine, phenylalanine, 2-hydroxypyridine, 2-aminopyridine, 2, 6-diaminopyridine, 2-methylpyridine, 3-aminopyridine, 4-methylpyridine, pentachloropyridine, 3-chloropyridine, 3-fluoropyridine, 3-bromopyridine, 2,3-diaminopyridine, 2-amino-3-chloropyridine, 2-pyrrolidone, 2-pyrrolecarboxylic acid, 3-acetyl-2,4-dimethylpyrrole, hydroxyethylpyrrolidone, 2-acetylpyrrole, 1-methylpyrrole, tetrahydropyrrole, ethyl pyrrole-2-carboxylate, 2,4-dimethylpyrrole, 4-acetylpyridine, 2-acetylpyrrole, N-methylpyrrole or deionized water.
[0038] Further, the metal chromium salt in the metal salt A in step 1) is one of the following: sodium chromate, potassium chromate, lead chromate, ammonium chromate, sodium dichromate, chromic anhydride, potassium dichromate, chromium oxide green, basic chromium sulfate;
[0039] The metal manganese salt in the metal salt A in step 1) is one of the following: manganese chloride, manganese sulfate, manganese nitrate, manganese carbonate, manganese acetate, manganese oxalate, manganese phosphate, manganese bromide, manganese iodide, manganese fluoride, manganese perchlorate, manganese citrate, manganous sulfate, manganous acetate, manganous oxalate, manganous hydrogen phosphate, manganese pyrophosphate, manganese silicate, manganese metasilicate;
[0040] The metal iron salt in the metal salt A in step 1) is one of the following: ferric sulfate, ferric chloride, ferric nitrate, ferric carbonate, ferrous sulfate, ferrous chloride, ferrous carbonate, ferric bromide, ferric perchlorate, ferric dihydrogen phosphate;
[0041] The metal vanadium salt in the metal salt A in step 1) is one of the following: ammonium metavanadate, sodium metavanadate, potassium metavanadate, sodium orthovanadate, vanadium chloride, vanadium oxide, vanadium tetrachloride, sodium vanadate, vanadium acetylacetonate, triisopropoxide vanadium, acetylacetonate vanadium, triisopropoxy vanadium oxide, vanadium diacetylacetonate oxide;
[0042] The metal cobalt salt in the metal salt A in step 1) is one of the following: cobalt chloride, cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt acetate, cobalt oxalate, cobalt phosphate, cobalt bromide, cobalt iodide, cobalt sulfide, cobalt fluoride, cobalt perchlorate, cobalt citrate, cobalt stearate, cobalt laurate, cobalt benzoate, ammonium cobalt chloride, ammonium cobalt sulfate, ammonium cobalt nitrate, cobalt hydrogen phosphate, cobaltous acetate;
[0043] The metal tungsten salt in the metal salt A in step 1) is one of the following: ammonium metatungstate, ammonium tungstate, potassium tungstate, sodium tungstate, phosphotungstic acid, sodium phosphotungstate, tungstosilicic acid, tungsten hexachloride, tungsten hexacarbonyl, tungsten isopropoxide;
[0044] The metal nickel salt in the metal salt A in step 1) is one of the following: nickel chloride, nickel acetylacetonate, nickel acetylacetonate, nickel acetate, nickel bromide, nickel iodide, nickel sulfate, nickel nitrate, nickel sulfate, nickel hypophosphite, nickel nitrate, nickel sulfamate, basic nickel carbonate, nickel formate, nickelocene, bis(triphenylphosphine)nickel bromide, bis(triphenylphosphine)nickel chloride;
[0045] The metal copper salt in the metal salt A in step 1) is one of the following: copper sulfate, copper chloride, copper carbonate, copper acetate, basic copper carbonate, copper gluconate, copper acetate, copper citrate;
[0046] The metal zinc salt in the metal salt A in step 1) is one of the following: zinc cyclohexanoate, zinc acetate, zinc acetate, methyl zinc, zinc oxide, zinc glycinate, zinc orotate, zinc picolinate, zinc gluconate, zinc sulfate;
[0047] The metal molybdenum salt in the metal salt A in step 1) is one of the following: molybdic acid, ammonium molybdate tetrahydrate, ammonium heptamolybdate, ammonium dimolybdate, sodium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, molybdenum chloride, lithium molybdate, potassium molybdenum hexacarbonyl, molybdenum acetylacetonate, and molybdenum isopropoxide;
[0048] The metal molybdenum salt in the metal salt B in the step 1) is one of the following: molybdic acid, ammonium molybdate tetrahydrate, ammonium heptamolybdate, ammonium dimolybdate, sodium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, molybdenum chloride, lithium molybdate, potassium molybdate, hexacarbonyl molybdenum, acetylacetonate molybdenum, isopropoxide molybdenum; the following types of metal salts B are selected because they include most of the non-precious metal elements in the fourth period, the fifth period and the sixth period, and the results obtained are universal.
[0049] The metal scandium salt in the metal salt B in step 1) is one of the following: scandium nitrate, scandium chloride, scandium sulfate, scandium acetate, scandium phosphate, scandium fluoride, scandium oxalate, and scandium carbonate;
[0050] The metal titanium salt in the metal salt B in step 1) is one of the following: titanic acid, titanium tetrachloride, titanium trichloride, titanium orthosulfate, titanyl sulfate, orthotitanic acid, sodium titanosilicate;
[0051] The metal vanadium salt in the metal salt B in step 1) is one of the following: ammonium metavanadate, sodium metavanadate, potassium metavanadate, sodium orthovanadate, vanadium chloride, vanadium oxide, vanadium tetrachloride, sodium vanadate, vanadium acetylacetonate, triisopropoxide vanadium, acetylacetonate vanadium, triisopropoxy vanadium oxide, vanadium diacetylacetonate oxide;
[0052] The metal chromium salt in the metal salt B in step 1) is one of the following: sodium chromate, potassium chromate, lead chromate, ammonium chromate, sodium dichromate, chromic anhydride, potassium dichromate, chromium oxide green, basic chromium sulfate;
[0053] The metal zinc salt in the metal salt B in step 1) is one of the following: zinc cyclohexanoate, zinc acetate, zinc acetate, methyl zinc, zinc oxide, zinc glycinate, zinc orotate, zinc picolinate, zinc gluconate, zinc sulfate;
[0054] The metal gallium salt in the metal salt B in step 1) is one of the following: gallium nitrate, gallium sulfate, gallium chloride, gallium fluoride, gallium hydroxide, and gallium acetate;
[0055] The metal germanium salt in the metal salt B in step 1) is one of the following: germanate, metagermanate, digermanate, tetragermanate;
[0056] The metal strontium salt in the metal salt B in step 1) is one of the following: strontium sulfate, strontium chloride, strontium nitrate, strontium carbonate, strontium hydroxide, strontium acetate;
[0057] The metal yttrium salt in the metal salt B in step 1) is one of the following: yttrium chloride, yttrium nitrate, yttrium sulfate, yttrium acetate, yttrium oxalate, yttrium fluoride;
[0058] The metal zirconium salt in the metal salt B in step 1) is one of the following: zirconium chloride, zirconium sulfate, zirconium carbonate, zirconium oxychloride, zirconium nitrate, zirconium acetate, zirconium fluoride;
[0059] The metal niobium salt in the metal salt B in step 1) is one of the following: niobium chloride, niobium fluoride, niobium pentachloride, niobium oxide, niobium oxalate;
[0060] The metal cadmium salt in the metal salt B in step 1) is one of the following: cadmium sulfate, cadmium chloride, cadmium nitrate, cadmium acetate, cadmium carbonate, cadmium iodide;
[0061] The metal indium salt in the metal salt B in step 1) is one of the following: indium chloride, indium nitrate, indium sulfate, indium iodide, indium acetate;
[0062] The metal tin salt in the metal salt B in step 1) is one of the following: tin chloride, tin sulfate, sodium stannate, tin fluoride, tin carbonate, tin acetate;
[0063] The metal antimony salt in the metal salt B in step 1) is one of the following: antimony chloride, antimony trioxide, potassium antimony tartrate, antimony acetate;
[0064] The metal hafnium salt in the metal salt B in step 1) is one of the following: hafnium chloride, hafnium fluoride, hafnium sulfate, hafnium nitrate, hafnium acetate, and hafnium oxide;
[0065] The metal tantalum salt in the metal salt B in step 1) is one of the following: tantalum chloride, potassium heptafluorotantalate, tantalum methanol, tantalum ethoxide, tantalum propoxide, tantalum butoxide, tantalum isobutoxide;
[0066] The metal tungsten salt in the metal salt B in step 1) is one of the following: ammonium metatungstate, ammonium tungstate, potassium tungstate, sodium tungstate, phosphotungstic acid, sodium phosphotungstate, tungstosilicic acid, tungsten hexachloride, tungsten hexacarbonyl, tungsten isopropoxide;
[0067] The metal rhenium salt in the metal salt B in step 1) is one of the following: rhenium heptoxide, rhenium dioxide, rhenium trioxide, rhenium disulfide, rhenium diboride, rhenium tetrafluoride, rhenium pentafluoride, and perrhenic acid;
[0068] The metal osmium salt of the metal salt B in step 1) is one of the following: osmium tetroxide, osmium dioxide, sodium hexachloroosmate, osmium disulfide, osmium ditelluride;
[0069] The metal lead salt in the metal salt B in step 1) is one of the following: lead nitrate, lead acetate, lead chloride, lead arsenate, lead oxide;
[0070] The metal bismuth salt in the metal salt B in step 1) is one of the following: bismuth nitrate, bismuth chloride, bismuth sulfate;
[0071] The metal lanthanum salt in the metal salt B in step 1) is one of the following: lanthanum nitrate, lanthanum chloride, lanthanum acetate, lanthanum sulfate;
[0072] The metal cerium salt in the metal salt B in step 1) is one of the following: cerium nitrate, cerium sulfate, cerium chloride, cerium oxalate;
[0073] The metal praseodymium salt in the metal salt B in step 1) is one of the following: praseodymium chloride, praseodymium oxide, praseodymium nitrate, praseodymium sulfate;
[0074] The metal neodymium salt in the metal salt B in step 1) is one of the following: neodymium nitrate, neodymium chloride, neodymium sulfate, and neodymium acetate;
[0075] The metal samarium salt in the metal salt B in step 1) is one of the following: samarium nitrate, samarium carbonate;
[0076] The metal europium salt in the metal salt B in step 1) is one of the following: europium fluoride, europium nitrate;
[0077] The metal gadolinium salt in the metal salt B in step 1) is one of the following: gadolinium sulfate, gadolinium nitrate;
[0078] The metal terbium salt in the metal salt B in step 1) is one of the following: terbium nitrate, terbium chloride, terbium sulfate;
[0079] The metal dysprosium salt in the metal salt B in step 1) is one of the following: dysprosium nitrate, dysprosium sulfate;
[0080] The metal holmium salt in the metal salt B in step 1) is one of the following: holmium chloride, holmium sulfate;
[0081] The metal erbium salt in the metal salt B in step 1) is one of the following: one of erbium nitrate, erbium chloride, and erbium sulfate;
[0082] The metal thulium salt in the metal salt B in step 1) is one of the following: thulium chloride, thulium nitrate;
[0083] The metal ytterbium salt in the metal salt B in step 1) is one of the following: ytterbium chloride and ytterbium sulfate.
[0084] Furthermore, the lignin in step 2) is one of the following: alkaline lignin, dealkalized lignin, sodium lignin sulfonate, sulfate lignin, hydrolyzed lignin, organosolv lignin, pyrolyzed lignin, enzymatic lignin, carboxymethylated lignin, aminated lignin, phosphorylated lignin, carboxylated lignin, sulfonated lignin or sulfurized lignin.
[0085] Furthermore, in step 2), the mixed solution D is first subjected to ultrasonic stirring and dispersion to completely dissolve to obtain a mixed suspension liquid, and then the mixed suspension liquid and the pretreated carrier are added to a reactor for solvothermal reaction. Lignin can be quickly dissolved by ultrasonic treatment.
[0086] The invention also discloses a lignin-derived carbon-alloy-metal oxide heterojunction catalyst, which is prepared by the above-mentioned preparation method.
[0087] Different from the prior art, the above technical solution has the following advantages: the present invention adopts the above solution, uses metal salt A and metal salt B as metal sources, and lignin as carbon source, firstly undergoes solvent thermal synthesis to make lignin and metal ions chelate and coordinate, and then undergoes high-temperature calcination reduction to obtain a lignin-derived carbon-alloy-metal oxide heterojunction catalyst. The catalyst prepared by the present invention has low cost and high activity, and has strong competitiveness in the fields of urea wastewater treatment and electrolytic hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 The XRD pattern of the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 of the present invention;
[0089] Figure 2 TEM image of the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 of the present invention;
[0090] Figure 3 The Raman data of the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 of the present invention;
[0091] Figure 4 The linear sweep voltammetry (LSV) curve data of hydrogen evolution of the catalyst prepared in Example 1 of the present invention and a 20wt.% commercial Pt / C catalyst in a mixed solution of 1.0mol / L potassium hydroxide and 0.5mol / L urea;
[0092] Figure 5 The Tafel slope curve data of the catalyst prepared in Example 1 of the present invention and a 20wt.% commercial Pt / C catalyst in a mixed solution of 1.0mol / L potassium hydroxide and 0.5mol / L urea;
[0093] Figure 6 LSV curve data of urea oxidation of the catalyst prepared in Example 1 of the present invention and a 40wt.% commercial RuO2 / C catalyst in a mixed solution of 1.0mol / L potassium hydroxide and 0.5mol / L urea;
[0094] Figure 7 These are the Tafel slope curve data of the catalyst prepared in Example 1 of the present invention and a 40 wt. % commercial RuO2 / C catalyst in a mixed solution of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea. DETAILED DESCRIPTION
[0095] In order to explain the technical content, structural features, achieved objectives and effects of the technical solution in detail, the following is a detailed description in conjunction with specific embodiments and accompanying drawings.
[0096] Example 1
[0097] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0098] (1) The untreated nickel mesh was rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water three times, each time for 30 minutes (surface area 9 cm 2 );
[0099] (2) dissolving 1.68 g of nickel nitrate (metal salt A) and 0.256 g of ammonium molybdate tetrahydrate (metal salt B) in 30 mL of deionized water to obtain a mixed solution C;
[0100] (3) 0.4 g of alkaline lignin (a commercial product purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand: L832292-100 g) was dissolved in the mixed solution C and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and the nickel mesh (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 180° C. The reaction was kept warm for 6 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out, filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0101] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 15% of the volume fraction of the mixed gas), heating to 500°C at a rate of 3°C / min, and continuing to keep warm for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0102] The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in this example was subjected to XRD detection, and the detected XRD pattern is shown in FIG. Figure 1 .
[0103] from Figure 1 It can be seen that the X-ray diffraction (XRD) standard cards corresponding to the catalyst prepared in this example are NiO (PDF#89-7131) and MoNi4 (PDF#65-5480), indicating that the lignin-derived carbon-alloy-metal oxide heterojunction catalyst was successfully prepared in this example.
[0104] The catalyst prepared in Example 1 was tested by transmission electron microscopes of different scales. Figure 2 ae. Among them, Figure 2 It can be seen from the ac that the lattice fringes of MoNi4 (310) and NiO (200) are 0.181nm and 0.209nm, respectively, indicating the successful preparation of lignin-derived carbon-alloy-metal oxide heterojunction catalysts. Figure 3 de shows that it has more mesoporous structures, which is beneficial to the gas-liquid transport of the catalyst to enhance the HER and UOR performance of the catalyst.
[0105] The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 was subjected to Raman spectroscopy (Raman) detection, and the detection data are shown in Figure 3 .
[0106] Depend on Figure 3 It can be seen that the D peak and the G peak are both Raman characteristic peaks of C, at 1350cm -1and 1580cm -1 This indicates that the catalyst prepared in this example has lignin-derived carbon.
[0107] Example 2
[0108] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0109] (1) The untreated copper mesh was rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water three times, each time for 30 minutes (surface area 9 cm 2 );
[0110] (2) dissolving 4.0 g of sodium dichromate and 0.8 g of scandium fluoride in 30 mL of ethanol to obtain a mixed solution C;
[0111] (3) 0.4 g of alkaline lignin (a commercial product purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand: L832292-100 g) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and a copper mesh (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 160°C for 8 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0112] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 15% of the volume fraction of the mixed gas), heating to 500°C at a rate of 3°C / min, and continuing to keep warm for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0113] Example 3
[0114] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0115] (1) The untreated nickel wire was rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water three times, each time for 30 minutes (surface area 9 cm 2 );
[0116] (2) dissolving 2.62 g of manganese phosphate and 0.2 g of titanium orthosulfate in 30 mL of ethylene glycol to obtain a mixed solution C;
[0117] (3) 0.4 g of sulfonated lignin (sulfonated or sulfomethylated at high temperature to introduce highly hydrophilic sulfonic acid groups into the alkaline lignin used in Example 1) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL, and the nickel wire (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 160°C for 6 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0118] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 10% of the volume fraction of the mixed gas), heating to 500°C at a rate of 5°C / min, and continuing to keep warm for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0119] Example 4
[0120] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0121] (1) The untreated nickel-iron wire was rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water three times, each time for 30 minutes (surface area 9 cm 2 );
[0122] (2) dissolving 1.68 g of sodium phosphotungstate, 1.68 g of cobalt phosphate and 0.256 g of vanadium chloride in 30 mL of isopropanol to obtain a mixed solution C;
[0123] (3) 0.4 g of sulfide lignin (alkaline lignin is sulfide-modified) is dissolved in the mixed solution, and ultrasonic stirring and dispersion are performed. The ultrasonication is performed for 10 min, and then stirring is performed for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid is placed in a reactor with a capacity of 50 mL, and the nickel-iron wire (surface area of 9 cm2) treated in step (1) is added. 2 ) was subjected to a solvent thermal reaction at a temperature of 160°C for 6 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0124] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 10% of the volume fraction of the mixed gas), heating to 400°C at a rate of 5°C / min, and continuing to keep warm for 5 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0125] Example 5
[0126] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0127] (1) The untreated zinc foil was rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water three times, each time for 30 minutes (surface area 9 cm 2 );
[0128] (2) dissolving 1.5 g of nickel iodide, 1.5 g of copper acetate and 0.256 g of ammonium chromate in 30 mL of methanol to obtain a mixed solution C;
[0129] (3) 0.4 g of sodium lignin sulfonate (a commercial product purchased from Tianjin Damao Chemical Reagent Factory, model: 8061-51-6) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL, and the zinc foil (surface area of 9 cm2) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 160°C for 6 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0130] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 15% of the volume fraction of the mixed gas), heating to 600°C at a rate of 10°C / min, and continuing to keep warm for 3 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0131] Example 6
[0132] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0133] (1) The untreated carbon nanotubes were washed with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water for 30 minutes each time (surface area 9 cm 2 );
[0134] (2) dissolving 1.35 g of zinc oxide, 1.35 g of chromic anhydride, and 0.3 g of cupric acetate in 30 mL of N,N-dimethylacetamide to obtain a mixed solution C;
[0135] (3) 0.4 g of kraft lignin (lignin extracted from kraft pulping black liquor, purchased from Shandong Sun Paper Co., Ltd.) was dissolved in the mixed solution and dispersed by ultrasonic stirring for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and the carbon nanotubes (surface area of 9 cm) treated in step (1) were added. 2 ) was subjected to a solvent thermal reaction at a temperature of 200°C for 4 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0136] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixed gas of hydrogen and argon (hydrogen accounts for 20% of the volume fraction of the mixed gas), raising the temperature to 700°C at a rate of 3°C / min, and continuing to keep the temperature for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0137] Example 7
[0138] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0139] (1) The untreated titanium mesh was rinsed with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water three times, each time for 30 minutes (surface area 9 cm 2 );
[0140] (2) dissolving 1.68 g of ferric nitrate, 1.68 g of manganese iodide, and 0.4 g of cobalt bromide in 30 mL of N-ethylaniline to obtain a mixed solution C;
[0141] (3) 0.4 g of enzymatic lignin (a byproduct of biomass fermentation to prepare fuel ethanol, purchased from Shandong Longli Technology Biotechnology Co., Ltd.) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and a titanium mesh (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 100°C for 24 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0142] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 40% of the volume fraction of the mixed gas), raising the temperature to 900°C at a rate of 10°C / min, and continuing to keep the temperature for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0143] Example 8
[0144] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0145] (1) The untreated graphene block was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water, each time for 20 minutes (surface area 9 cm 2 );
[0146] (2) 1.0 g of tungsten hexachloride, 1.0 g of cobalt hydrogen phosphate, and 0.2 g of zinc acetate were dissolved in 30 mL of n-butanol to obtain a mixed solution C;
[0147] (3) 0.4 g of dealkalized lignin (a commercial product purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model: L195713-100 g) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL, and the graphene block (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 140°C for 10 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0148] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 45% of the volume fraction of the mixed gas), heating to 1000°C at a rate of 10°C / min, and continuing to keep warm for 3 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0149] Example 9
[0150] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0151] (1) The untreated nickel-molybdenum wire was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water, respectively, for 30 minutes each time (surface area 9 cm 2 );
[0152] (2) dissolving 1.5 g of nickel formate, 1.5 g of zinc acetate, and 0.32 g of digermanate in 30 mL of toluene to obtain a mixed solution C;
[0153] (3) 0.4 g of hydrolyzed lignin (hydrolyzed lignin is lignin obtained by hydrolyzing plant fiber raw materials to remove cellulose and hemicellulose, purchased from Shandong Sun Paper Co., Ltd.) was dissolved in the mixed solution and subjected to ultrasonic stirring and dispersion, first ultrasonicating for 10 min, then stirring for 10 min to obtain a mixed suspension liquid, and the mixed suspension liquid was placed in a reactor with a capacity of 50 mL, and the nickel-molybdenum wire (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 180°C for 6 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0154] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 50% of the volume fraction of the mixed gas), heating to 1000°C at a rate of 15°C / min, and continuing to keep warm for 1 hour for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0155] Example 10
[0156] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0157] (1) The untreated iron foil was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water, respectively, for 30 minutes each time (surface area 9 cm 2 );
[0158] (2) dissolving 1.4 g of chromium oxide green, 1.4 g of cobalt bromide, and 0.256 g of gallium fluoride in 30 mL of polyethylene glycol to obtain a mixed solution C;
[0159] (3) 0.4 g of dealkalized lignin (a commercial product purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model: L195713-100 g) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL, and the iron foil (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 150°C for 10 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0160] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixed gas of hydrogen and argon (hydrogen accounts for 50% of the volume fraction of the mixed gas), raising the temperature to 500°C at a rate of 10°C / min, and continuing to keep the temperature for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0161] Embodiment 11
[0162] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0163] (1) The untreated carbon fiber sheet was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water, respectively, for 30 minutes each time (surface area 9 cm 2 );
[0164] (2) 1.68 g of ferric chloride, 1.68 g of tungsten isopropoxide, and 0.256 g of yttrium oxalate were dissolved in 30 mL of 2,6-diaminopyridine-2-methylpyridine to obtain a mixed solution C;
[0165] (3) 0.4 g of phosphorylated lignin (the alkaline lignin used in Example 1 was phosphorylated and modified) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and the carbon fiber sheet (surface area of 9 cm2) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 160°C for 10 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0166] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 30% of the volume fraction of the mixed gas), heating to 700°C at a rate of 5°C / min, and continuing to keep warm for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0167] Example 12
[0168] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0169] (1) The untreated copper sheet was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water, each time for 30 minutes (surface area 9 cm 2 );
[0170] (2) dissolving 1.35 g of molybdenum chloride, 1.35 g of nickel bromide, and 0.5 g of zirconium acetate in 30 mL of 3-aminopyridine to obtain a mixed solution C;
[0171] (3) 0.4 g of carboxylated lignin (the alkaline lignin of Example 1 was carboxylated) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension. The mixed suspension was placed in a reactor with a capacity of 50 mL and the copper sheet (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 150°C for 8 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0172] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 20% of the volume fraction of the mixed gas), heating to 700°C at a rate of 5°C / min, and continuing to keep warm for 3 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0173] Embodiment 13
[0174] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0175] (1) The untreated stainless steel sheet was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water, respectively, for 30 minutes each time (surface area 9 cm 2 );
[0176] (2) dissolving 1.38 g of cobalt laurate, 1.38 g of copper acetate, and 0.4 g of niobium chloride in 30 mL of 2,3-diaminopyridine to obtain a mixed solution C;
[0177] (3) 0.4 g of alkaline lignin (a commercial product purchased from Shanghai MacLean Biochemical Technology Co., Ltd., model: L832292-100 g) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and a stainless steel sheet (surface area of 9 cm) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 170°C for 10 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0178] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 45% of the volume fraction of the mixed gas), heating to 600°C at a rate of 6°C / min, and continuing to keep warm for 2 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0179] Embodiment 14
[0180] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0181] (1) The untreated cobalt mesh was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid, and deionized water, each time for 30 minutes (surface area 9 cm 2 );
[0182] (2) dissolving 1.3 g of zinc glycinate, 1.3 g of ammonium dimolybdate, and 0.25 g of indium chloride in 30 mL of 2-amino-3-chloropyridine to obtain a mixed solution C;
[0183] (3) 0.5% aminated lignin (the alkaline lignin of Example 1 was aminated) was dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture was first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid was placed in a reactor with a capacity of 50 mL and the cobalt mesh (surface area of 9 cm2) treated in step (1) was added. 2 ) was subjected to a solvent thermal reaction at a temperature of 150°C for 10 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0184] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 25% of the volume fraction of the mixed gas), heating to 500°C at a rate of 5°C / min, and continuing to keep warm for 3 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0185] Embodiment 15
[0186] A lignin-derived carbon-alloy-metal oxide heterojunction catalyst is prepared by the following method:
[0187] (1) The untreated activated carbon block was rinsed twice with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water, each time for 30 minutes (surface area 9 cm 2 );
[0188] (2) dissolving 1.2 g of sodium orthovanadate, 1.2 g of manganese hydrogen phosphate, and 0.35 g of hafnium chloride in 30 mL of N-methylpyrrole to obtain a mixed solution C;
[0189] (3) 0.4 g of carboxylated lignin (the alkaline lignin of Example 1 is carboxylated) is dissolved in the mixed solution and dispersed by ultrasonic stirring. The mixture is first ultrasonicated for 10 min and then stirred for 10 min to obtain a mixed suspension liquid. The mixed suspension liquid is placed in a reactor with a capacity of 50 mL and the activated carbon block (surface area of 9 cm2) treated in step (1) is added. 2 ) was subjected to a solvent thermal reaction at a temperature of 150°C for 10 hours. After natural cooling, the product obtained after the solvent thermal reaction was taken out and filtered, washed, and vacuum dried for 24 hours to obtain a primary sample.
[0190] (4) placing the primary sample obtained in step (3) in a tubular furnace, introducing a mixture of hydrogen and argon (hydrogen accounting for 50% of the volume fraction of the mixed gas), heating to 400°C at a rate of 10°C / min, and continuing to keep warm for 5 hours for high-temperature calcination to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
[0191] The lignin-derived carbon-alloy-metal oxide heterojunction catalysts prepared in Examples 1-15 were subjected to HER and UOR tests in 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solutions, and the specific operations were as follows:
[0192] (1) The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Examples 1-15 was used as a working electrode, and electrochemical testing was performed using an electrochemical workstation.
[0193] (2) The test conditions are as follows: a carbon rod is used as a counter electrode, a mercury / mercury oxide electrode is used as a reference electrode, and the catalysts prepared in Examples 1-15 are used as working electrodes, respectively, to form 15 sets of three-electrode test systems. Then, the HER and UOR electrochemical performance tests are carried out in an alkaline medium of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution. The results are shown in Tables 1 and 2.
[0194] Table 1 HER electrochemical performance in a mixed solution of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea
[0195]
[0196] Table 2 UOR electrochemical performance in a mixed solution of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea
[0197]
[0198] As can be seen from Table 1, 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution were used as electrolytes for detection. -2 At a potential of -500 mA cm, the electrochemical hydrogen evolution performance of the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared by the present invention is as high as -39 mV in Example 1 and as low as -98 mV in Example 8; -2 At a potential of -1000 mA cm, the electrochemical hydrogen evolution performance of the catalyst prepared by the present invention is as high as -390 mV in Example 8 and as low as -262 mV in Example 1; -2 At a potential of , the electrochemical hydrogen evolution performance of the catalyst prepared by the present invention is as high as -503 mV in Example 8 and as low as -356 mV in Example 1. At the same time, the minimum Tafel slope is 64.35 mVdec in Example 1. -1 ; The maximum value is 99.64mV dec in Example 8 -1 According to the test performance in Table 1, the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared by the present invention has good HER performance in an alkaline medium of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution. It can be seen from the above test data that Example 1 is the best example of the present invention.
[0199] As can be seen from Table 2, 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution alkaline medium were used as electrolytes for detection. -2 At a potential of 500 mA cm, the electrochemical UOR performance of the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared by the present invention is as high as 1.33 V in Example 10 and as low as 1.28 V in Example 1; -2 At a potential of 1000 mA cm, the electrochemical hydrogen evolution performance of the catalyst prepared by the present invention is as high as 1.49 V in Example 10 and as low as 1.40 V in Example 1; -2 At the potential of , the electrochemical UOR performance of the catalyst prepared by the present invention is the highest 1.65V of Example 10 and the lowest 1.46V of Example 1. At the same time, the minimum Tafel slope is 41.42mV dec of Example 1. -1 ; The maximum value is 80.56mV dec of Example 10 -1 According to the test performance in Table 2, the lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared by the present invention has good UOR performance in 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution. And from the above test data, it can be seen that Example 1 is the best example of the present invention.
[0200] The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 and 20 wt.% of commercial Pt / C catalyst were subjected to hydrogen evolution linear sweep voltammetry (LSV) detection in 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution. The scanned curve data are shown in Figure 4 .
[0201] Depend on Figure 4 It can be seen that the LSV curve proves the electrochemical performance of the catalyst prepared in this example. Combined with the data in Table 1, it can be seen that at the same current density, the smaller the overpotential, the better the HER performance of the catalyst. -2 Under the potential, the overpotential of the catalyst prepared in the present invention is close to the overpotential of the commercial Pt / C catalyst, indicating that the HER electrochemical performance of the catalyst prepared in this example is equivalent to that of the commercial Pt / C catalyst.
[0202] The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 and a 20 wt.% commercial Pt / C catalyst were subjected to Tafel slope detection in a 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution. The detected curve data are shown in FIG. Figure 5 .
[0203] The Tafel slope is obtained by changing the LSV formula. At the same time, the Tafel slope represents the speed of the reaction kinetics. Figure 5 Combined with the data in Table 1, it can be seen that the smaller the Tafel slope value, the faster the reaction kinetics; the larger the Tafel slope value, the slower the reaction kinetics. In the alkaline medium of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution, the Tafel slope of the catalyst prepared in this example is close to that of the commercial Pt / C catalyst, indicating that the reaction kinetics of the catalyst prepared in this example is comparable to that of the commercial Pt / C catalyst.
[0204] The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 and 40 wt.% of commercial RuO2 / C catalyst were subjected to linear sweep voltammetry (LSV) detection of hydrogen evolution in 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution. The scanned curve data are shown in FIG. Figure 6 .
[0205] Figure 6 The LSV curve can prove the electrochemical performance of the catalyst prepared in this example. Combined with the data in Table 2, it can be seen that at the same current density, the smaller the potential, the better the UOR performance of the catalyst. -2Under the potential, the overpotential of the catalyst prepared in this embodiment is close to the overpotential of the commercial RuO2 / C catalyst, indicating that the HER electrochemical performance of the catalyst prepared in the present invention is equivalent to that of the commercial RuO2 / C catalyst.
[0206] The lignin-derived carbon-alloy-metal oxide heterojunction catalyst prepared in Example 1 and 40 wt.% of commercial RuO2 / C catalyst were subjected to Tafel slope detection in a mixed solution of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea. The detected curve data are shown in FIG. Figure 7 .
[0207] The Tafel slope is obtained by changing the LSV formula. At the same time, the Tafel slope represents the speed of the reaction kinetics. Figure 7 Combined with the data in Table 2, it can be seen that the smaller the Tafel slope value, the faster the reaction kinetics; the larger the Tafel slope value, the slower the reaction kinetics. In the alkaline medium of 1.0 mol / L potassium hydroxide and 0.5 mol / L urea solution, the Tafel slope of the catalyst prepared in this example is close to that of the commercial RuO2 / C catalyst, indicating that the reaction kinetics of the catalyst prepared in the present invention is comparable to that of the commercial RuO2 / C catalyst.
[0208] It should be noted that, although the above embodiments have been described in this article, the patent protection scope of the present invention is not limited thereby. Therefore, based on the innovative concept of the present invention, changes and modifications made to the embodiments described herein, or equivalent structures or equivalent process changes made using the contents of the present invention specification and drawings, directly or indirectly applying the above technical solutions to other related technical fields, are all included in the patent protection scope of the present invention.
Claims
1. A method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst, characterized in that: It includes the following steps: 1) dissolving metal salt A and metal salt B in an organic solvent to obtain a mixed solution C; The metal salt A is one or a mixture of two or more of the following: chromium salt, manganese salt, iron salt, nickel salt, vanadium salt, cobalt salt, tungsten salt, copper salt, zinc salt, or molybdenum salt; The metal salt B is one of the following: molybdenum salt, scandium salt, titanium salt, vanadium salt, chromium salt, zinc salt, gallium salt, germanium salt, strontium salt, yttrium salt, zirconium salt, niobium salt, cadmium salt, indium salt, tin salt, antimony salt, hafnium salt, tantalum salt, tungsten salt, rhenium salt, osmium salt, thallium salt, lead salt, bismuth salt, lanthanum salt, cerium salt, praseodymium salt, neodymium salt, samarium salt, europium salt, gadolinium salt, terbium salt, dysprosium salt, holmium salt, erbium salt, ytterbium salt or thulium salt; The metal salt A and the metal salt B are different types of metal salts; 2) dissolving lignin in the mixed solution C to obtain a mixed solution D, then adding the mixed solution D and the pretreated carrier into a reactor for a solvothermal reaction at a reaction temperature of 100-200° C. for a reaction time of 4-24 hours, cooling to room temperature after the reaction is completed, taking out the reaction solution in the reactor for filtering, washing the filter cake, and drying to obtain a preliminary sample; The input mass ratio of the metal salt A, metal salt B and lignin is 10-26.2:2:1-4; The ratio of the input mass of the metal salt A to the surface area of the pretreated carrier is 1-4:9 mg / cm 2 ; 3) placing the preliminary sample prepared in step 2) in a calcining furnace, introducing a mixed gas of hydrogen and argon, wherein the volume fraction of hydrogen in the mixed gas is 10-50%, heating the mixture to 400-1000°C at a heating rate of 3-15°C / min, and calcining the mixture at high temperature for 1-5 hours to obtain the lignin-derived carbon-alloy-metal oxide heterojunction catalyst.
2. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: The carrier in step 1) is a metal carrier or a non-metal carrier, and the metal carrier is one of the following: a metal mesh, a metal sheet, a metal wire, a metal foil, an alloy mesh, an alloy sheet, or an alloy wire.
3. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 2, characterized in that: The metal mesh is one of the following: nickel mesh, cobalt mesh, copper mesh, iron mesh, titanium mesh; The alloy mesh is a nickel-iron mesh or a nickel-molybdenum mesh; The metal sheet is one of the following: nickel sheet, cobalt sheet, copper sheet, iron sheet, titanium sheet; The alloy sheet is one of the following: nickel-cobalt sheet, nickel-copper sheet, iron-copper sheet, nickel-iron sheet, stainless steel sheet, nickel-molybdenum sheet or nickel-chromium sheet; The metal wire is one of the following: nickel wire, cobalt wire, copper wire, iron wire, aluminum wire, titanium wire; The alloy wire is nickel-iron wire or nickel-molybdenum wire; The metal foil is one of the following: nickel foil, cobalt foil, copper foil, iron foil, zinc foil or titanium foil; The non-metallic carrier is one of the following: carbon black tube, carbon nanotube, carbon fiber sheet, activated carbon fiber sheet, carbon nanorod, graphene block, graphene oxide block, activated carbon block, porous carbon block, carbon cloth, carbon felt, glass fiber mesh, layered graphite, organic glass or expanded perlite.
4. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: In the step 3), after the preliminary sample is placed in a calcining furnace for calcination, two or more metal salts A are calcined to form an alloy, or more than one metal salt A and part of the metal salt B are calcined to form an alloy, and the formed alloy is one or a mixture of two or more of the following: NiCo, MoNi, NiFe, NiMn, NiCu, NiCr, NiZn, NiV, NiW, CuCo, CuZn, CuMo, CuFe, CuMn, CuV, CuW, FeCr, FeMn, FeCo, FeZn, FeV, FeW, CoMn, CoZn, CoMo, CoCr, CoV, CoW, NiCoCu, CoCrMo, NiCoMo, NiFeMo, NiMnMo, NiCrMo, NiCuMo, NiCoFe, NiCoZn, NiCoCr, NiCoMn, NiCoV, NiCoW; In the step 3), after the preliminary sample is placed in a calcination furnace for calcination, the metal salt B is calcined to form a metal oxide, the metal oxide forms a heterojunction and is loaded on a self-supporting carrier, and the formed metal oxide is one of the following: MoO2, Sc2O3, TiO2, V2O5, CrO3, ZnO, Ga2O3, GeO2, SrO, Y2O3, ZrO2, Nb2O5, CdO, In2O3, SnO2, Sb2O5, HfO2, Ta2O5, WO2, ReO3, OsO2, Tl2O3, Pb3O4, Bi2O3, La2O3, CeO2, Pr2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3.
5. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: The pretreatment method of the carrier is: the untreated carrier is washed with anhydrous ethanol, 1.0 mol / L hydrochloric acid and deionized water in sequence, each washing is performed 3 times, and the washing time of each washing is 20-30 minutes.
6. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: The solvent added in step 1) is one of the following: ethanol, ethylene glycol, methanol, isopropanol, glycerol, n-butanol, N,N-dimethylformamide, oleylamine, oleic acid, polyethylene glycol, toluene, acetonitrile, N,N-dimethylacetamide, dimethyl sulfoxide, pyridine, pyrrole, urea, aniline, N-methylaniline, N,N-dimethylaniline, N-ethylaniline, N,N-diethylaniline, diphenylamine, aniline hydrochloride, dioxydimethylpurine, phenylalanine, 2-hydroxypyridine, 2-aminopyridine, 2,6- Diaminopyridine 2-methylpyridine, 3-aminopyridine, 4-methylpyridine, pentachloropyridine, 3-chloropyridine, 3-fluoropyridine, 3-bromopyridine, 2,3-diaminopyridine, 2-amino-3-chloropyridine, 2-pyrrolidone, 2-pyrrolecarboxylic acid, 3-acetyl-2,4-dimethylpyrrole, hydroxyethylpyrrolidone, 2-acetylpyrrole, 1-methylpyrrole, tetrahydropyrrole, ethyl pyrrole-2-carboxylate, 2,4-dimethylpyrrole, 4-acetylpyridine, 2-acetylpyrrole, N-methylpyrrole or deionized water.
7. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: The metal chromium salt in the metal salt A in step 1) is one of the following: sodium chromate, potassium chromate, lead chromate, ammonium chromate, sodium dichromate, chromic anhydride, potassium dichromate, chromium oxide green, basic chromium sulfate; The metal manganese salt in the metal salt A in step 1) is one of the following: manganese chloride, manganese sulfate, manganese nitrate, manganese carbonate, manganese acetate, manganese oxalate, manganese phosphate, manganese bromide, manganese iodide, manganese fluoride, manganese perchlorate, manganese citrate, manganous sulfate, manganous acetate, manganous oxalate, manganous hydrogen phosphate, manganese pyrophosphate, manganese silicate, manganese metasilicate; The metal iron salt in the metal salt A in step 1) is one of the following: ferric sulfate, ferric chloride, ferric nitrate, ferric carbonate, ferrous sulfate, ferrous chloride, ferrous carbonate, ferric bromide, ferric perchlorate, ferric dihydrogen phosphate; The metal vanadium salt in the metal salt A in step 1) is one of the following: ammonium metavanadate, sodium metavanadate, potassium metavanadate, sodium orthovanadate, vanadium chloride, vanadium oxide, vanadium tetrachloride, sodium vanadate, vanadium acetylacetonate, triisopropoxide vanadium, acetylacetonate vanadium, triisopropoxy vanadium oxide, vanadium diacetylacetonate oxide; The metal cobalt salt in the metal salt A in step 1) is one of the following: cobalt chloride, cobalt sulfate, cobalt nitrate, cobalt carbonate, cobalt acetate, cobalt oxalate, cobalt phosphate, cobalt bromide, cobalt iodide, cobalt sulfide, cobalt fluoride, cobalt perchlorate, cobalt citrate, cobalt stearate, cobalt laurate, cobalt benzoate, ammonium cobalt chloride, ammonium cobalt sulfate, ammonium cobalt nitrate, cobalt hydrogen phosphate, cobaltous acetate; The metal tungsten salt in the metal salt A in step 1) is one of the following: ammonium metatungstate, ammonium tungstate, potassium tungstate, sodium tungstate, phosphotungstic acid, sodium phosphotungstate, tungstosilicic acid, tungsten hexachloride, tungsten hexacarbonyl, tungsten isopropoxide; The metal nickel salt in the metal salt A in step 1) is one of the following: nickel chloride, nickel acetylacetonate, nickel acetylacetonate, nickel acetate, nickel bromide, nickel iodide, nickel sulfate, nickel nitrate, nickel sulfate, nickel hypophosphite, nickel nitrate, nickel sulfamate, basic nickel carbonate, nickel formate, nickelocene, bis(triphenylphosphine)nickel bromide, bis(triphenylphosphine)nickel chloride; The metal copper salt in the metal salt A in step 1) is one of the following: copper sulfate, copper chloride, copper carbonate, copper acetate, basic copper carbonate, copper gluconate, copper acetate, copper citrate; The metal zinc salt in the metal salt A in step 1) is one of the following: zinc cyclohexanoate, zinc acetate, zinc acetate, methyl zinc, zinc oxide, zinc glycinate, zinc orotate, zinc picolinate, zinc gluconate, zinc sulfate; The metal molybdenum salt in the metal salt A in step 1) is one of the following: molybdic acid, ammonium molybdate tetrahydrate, ammonium heptamolybdate, ammonium dimolybdate, sodium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, molybdenum chloride, lithium molybdate, potassium molybdenum hexacarbonyl, molybdenum acetylacetonate, and molybdenum isopropoxide; The metal molybdenum salt in the metal salt B in the step 1) is one of the following: molybdic acid, ammonium molybdate tetrahydrate, ammonium heptamolybdate, ammonium dimolybdate, sodium molybdate, phosphomolybdic acid, ammonium phosphomolybdate, sodium phosphomolybdate, molybdenum chloride, lithium molybdate, potassium molybdenum hexacarbonyl, molybdenum acetylacetonate, and molybdenum isopropoxide; The metal scandium salt in the metal salt B in step 1) is one of the following: scandium nitrate, scandium chloride, scandium sulfate, scandium acetate, scandium phosphate, scandium fluoride, scandium oxalate, and scandium carbonate; The metal titanium salt in the metal salt B in step 1) is one of the following: titanic acid, titanium tetrachloride, titanium trichloride, titanium orthosulfate, titanyl sulfate, orthotitanic acid, sodium titanosilicate; The metal vanadium salt in the metal salt B in step 1) is one of the following: ammonium metavanadate, sodium metavanadate, potassium metavanadate, sodium orthovanadate, vanadium chloride, vanadium oxide, vanadium tetrachloride, sodium vanadate, vanadium acetylacetonate, triisopropoxide vanadium, acetylacetonate vanadium, triisopropoxy vanadium oxide, vanadium diacetylacetonate oxide; The metal chromium salt in the metal salt B in step 1) is one of the following: sodium chromate, potassium chromate, lead chromate, ammonium chromate, sodium dichromate, chromic anhydride, potassium dichromate, chromium oxide green, basic chromium sulfate; The metal zinc salt in the metal salt B in step 1) is one of the following: zinc cyclohexanoate, zinc acetate, zinc acetate, methyl zinc, zinc oxide, zinc glycinate, zinc orotate, zinc picolinate, zinc gluconate, zinc sulfate; The metal gallium salt in the metal salt B in step 1) is one of the following: gallium nitrate, gallium sulfate, gallium chloride, gallium fluoride, gallium hydroxide, and gallium acetate; The metal germanium salt in the metal salt B in step 1) is one of the following: germanate, metagermanate, digermanate, tetragermanate; The metal strontium salt in the metal salt B in step 1) is one of the following: strontium sulfate, strontium chloride, strontium nitrate, strontium carbonate, strontium hydroxide, strontium acetate; The metal yttrium salt in the metal salt B in step 1) is one of the following: yttrium chloride, yttrium nitrate, yttrium sulfate, yttrium acetate, yttrium oxalate, yttrium fluoride; The metal zirconium salt in the metal salt B in step 1) is one of the following: zirconium chloride, zirconium sulfate, zirconium carbonate, zirconium oxychloride, zirconium nitrate, zirconium acetate, zirconium fluoride; The metal niobium salt in the metal salt B in step 1) is one of the following: niobium chloride, niobium fluoride, niobium pentachloride, niobium oxide, niobium oxalate; The metal cadmium salt in the metal salt B in step 1) is one of the following: cadmium sulfate, cadmium chloride, cadmium nitrate, cadmium acetate, cadmium carbonate, cadmium iodide; The metal indium salt in the metal salt B in step 1) is one of the following: indium chloride, indium nitrate, indium sulfate, indium iodide, indium acetate; The metal tin salt in the metal salt B in step 1) is one of the following: tin chloride, tin sulfate, sodium stannate, tin fluoride, tin carbonate, tin acetate; The metal antimony salt in the metal salt B in step 1) is one of the following: antimony chloride, antimony trioxide, potassium antimony tartrate, antimony acetate; The metal hafnium salt in the metal salt B in step 1) is one of the following: hafnium chloride, hafnium fluoride, hafnium sulfate, hafnium nitrate, hafnium acetate, and hafnium oxide; The metal tantalum salt in the metal salt B in step 1) is one of the following: tantalum chloride, potassium heptafluorotantalate, tantalum methanol, tantalum ethoxide, tantalum propoxide, tantalum butoxide, tantalum isobutoxide; The metal tungsten salt in the metal salt B in step 1) is one of the following: ammonium metatungstate, ammonium tungstate, potassium tungstate, sodium tungstate, phosphotungstic acid, sodium phosphotungstate, tungstosilicic acid, tungsten hexachloride, tungsten hexacarbonyl, tungsten isopropoxide; The metal rhenium salt in the metal salt B in step 1) is one of the following: rhenium heptoxide, rhenium dioxide, rhenium trioxide, rhenium disulfide, rhenium diboride, rhenium tetrafluoride, rhenium pentafluoride, and perrhenic acid; The metal osmium salt in the metal salt B in step 1) is one of the following: osmium tetroxide, osmium dioxide, sodium hexachloroosmate, osmium disulfide, osmium ditelluride; The metal lead salt in the metal salt B in step 1) is one of the following: lead nitrate, lead acetate, lead chloride, lead arsenate, lead oxide; The metal bismuth salt in the metal salt B in step 1) is one of the following: bismuth nitrate, bismuth chloride, bismuth sulfate; The metal lanthanum salt in the metal salt B in step 1) is one of the following: lanthanum nitrate, lanthanum chloride, lanthanum acetate, lanthanum sulfate; The metal cerium salt in the metal salt B in step 1) is one of the following: cerium nitrate, cerium sulfate, cerium chloride, cerium oxalate; The metal praseodymium salt in the metal salt B in step 1) is one of the following: praseodymium chloride, praseodymium oxide, praseodymium nitrate, praseodymium sulfate; The metal neodymium salt in the metal salt B in step 1) is one of the following: neodymium nitrate, neodymium chloride, neodymium sulfate, and neodymium acetate; The metal samarium salt in the metal salt B in step 1) is one of the following: samarium nitrate, samarium carbonate; The metal europium salt in the metal salt B in step 1) is one of the following: europium fluoride, europium nitrate; The metal gadolinium salt in the metal salt B in step 1) is one of the following: gadolinium sulfate, gadolinium nitrate; The metal terbium salt in the metal salt B in step 1) is one of the following: terbium nitrate, terbium chloride, terbium sulfate; The metal dysprosium salt in the metal salt B in step 1) is one of the following: dysprosium nitrate, dysprosium sulfate; The metal holmium salt in the metal salt B in step 1) is one of the following: holmium chloride, holmium sulfate; The metal erbium salt in the metal salt B in step 1) is one of the following: one of erbium nitrate, erbium chloride, and erbium sulfate; The metal thulium salt in the metal salt B in step 1) is one of the following: thulium chloride, thulium nitrate; The metal ytterbium salt in the metal salt B in step 1) is one of the following: ytterbium chloride and ytterbium sulfate.
8. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: The lignin in step 2) is one of the following: alkaline lignin, dealkalized lignin, sodium lignin sulfonate, sulfate lignin, hydrolyzed lignin, organic solvent lignin, pyrolyzed lignin, enzymatic lignin, carboxymethylated lignin, aminated lignin, phosphorylated lignin, carboxylated lignin, sulfonated lignin or sulfurized lignin.
9. The method for preparing a lignin-derived carbon-alloy-metal oxide heterojunction catalyst according to claim 1, characterized in that: In the step 2), the mixed solution D is first subjected to ultrasonic stirring and dispersion to completely dissolve to obtain a mixed suspension liquid, and then the mixed suspension liquid and the pretreated carrier are added together into a reactor to perform a solvothermal reaction.
10. A lignin-derived carbon-alloy-metal oxide heterojunction catalyst, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Highly dispersed lignin-derived Ru in-situ N-doped carbon material and preparation method and application thereof
CN117239156B
Lignin-based tri-metal nitrogen-doped carbon material as well as preparation method and application thereof
CN114196989A
Preparation method of lignin-based bimetallic catalyst and application of lignin-based bimetallic catalyst in hydrogen evolution by electrolyzing water
CN114875443A
Molybdenum-doped nickel-cobalt-copper lattice stretching alloy catalyst and preparation method thereof
CN117199398A
Lignin-based Ru / Co bimetallic in-situ N-doped carbon material as well as preparation method and application thereof
CN117230479A
Cited By
High-activity catalyst for producing hydrogen by electrolyzing water as well as preparation method and application of high-activity catalyst
CN120989664A